2020
DOI: 10.1021/acs.est.0c04386
|View full text |Cite
|
Sign up to set email alerts
|

A Very Hungry Caterpillar: Polyethylene Metabolism and Lipid Homeostasis in Larvae of the Greater Wax Moth (Galleria mellonella)

Abstract: Larvae of the greater wax moth (Galleria mellonella) possess the remarkable ability to consume and rapidly degrade low-density polyethylene. Previous studies have investigated the involvement of the animal’s microbiome, but little is known about the host’s actual role and if it benefits from biodegradation of this synthetic polymer. We used a combination of RNA sequencing and biochemical approaches to assess caterpillars fed honeycomb, fed polyethylene (PE), or starved for up to 72 h. Sequencing of gut transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…24 Lemoine reported a 50% weight low on a PE diet. 25 Our results suggested that a pollen-only diet is sufficient for the survival of the larvae and that an additional source of carbon such as beeswax allows larvae to gain weight, in agreement with the literature 17,14 . L2-L3 larvae fed with pollen and PE survived 16 days and gained some weight but far less than the larvae fed with the optimal diet.…”
Section: Discussionsupporting
confidence: 91%
“…24 Lemoine reported a 50% weight low on a PE diet. 25 Our results suggested that a pollen-only diet is sufficient for the survival of the larvae and that an additional source of carbon such as beeswax allows larvae to gain weight, in agreement with the literature 17,14 . L2-L3 larvae fed with pollen and PE survived 16 days and gained some weight but far less than the larvae fed with the optimal diet.…”
Section: Discussionsupporting
confidence: 91%
“…It has the advantages of being inexpensive, easy to use, and able to grow at 37 °C, while not being subject to the same regulations and ethical concerns as mammalian models such as mice [15–17]. It has also been of interest due to the ability of the larvae to metabolize polyethylene [18]. Previous research on endogenous Galleria and Enterococcus species indicates these bacteria may have a colonization-resistance function, either passively or actively, through the production of antimicrobial bacteriocins [11, 19].…”
Section: Introductionmentioning
confidence: 99%
“…While plastics do not occur naturally, nature has a solution to man's artificial problem in the insects. These biological expertise include: Tenebrio molitor [36][37][38], Zophobas morio [35,36,39] and waxworms (Galleria mellonella L.) [40,41] to utilize PS and PE for mineralization [35,36,[39][40][41] as a carbon source. Fully digested, their frass can be utilized as natural fertilizers.…”
Section: Zophobas Morio and Tenebrio Molitor In The Circular Economymentioning
confidence: 99%